The nth term is: 3n+1 and so the next number will be 16
It is: 3n+1
The nth term is: 5-6n
The nth term is 6n+1 and so the next term will be 31
Tn = 1 + 3n
nth term= 6 + (n-1) (2)
13 n 5
[ 25 - 6n ] is.
I suspect that the first term should be "negative 3", ie the sequence is -3, 1, 5, 9, 13, 17, ... The nth term is 4n - 7
This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term
The nth term in this arithmetic sequence is an=26+(n-1)(-8).
The nth term is 4n - 3
The nth term is: 5-2n
This is an arithmetic sequence which starts at 14, a = 14, and with a common difference of -1, d = -1. We can use the nth term formula an = a + (n - 1)d to get an = 14 + (n - 1)(-1) = 14 - n + 1 = 15 - n.
t(3) = 10 - 32 = 1
T(n) = 25 - 6n
2n + 1
This is an Arithmetic Series/Sequence. In general the nth term, A(n) = a + (n - 1)d....where a is the 1st term and d is the common difference. In this question, the 1st term equals 1 and the common difference is 4. Then the nth term, A(n) = 1 + (n - 1) x 4 = 1 + 4n - 4 = 4n - 3.
One possibility: 3n + 1